Poroid hidradenoma of the scalp in an immunosuppressed patient - Grant, Matthew T (J Surg Case Rep, 2019)
We discuss the rare finding of what initially presented as a common subcutaneous scalp nodule. Yet, after surgical excision, the lesion was found to be a poroid hidradenoma (PH). PH is a rare variant of poroid neoplasms. PH, when observed, is commonly associated with the head and neck. However, it is rarely described in literature beyond the dermatopathologic findings. Here, we describe the clinical presentation of a unique case of a scalp PH in the setting of immunosuppression.